Evaluation and comparison of mechanical properties of lithium disilicate-based CAD/CAM blocks - Sofya Zulkiffli,; Yeoh, Oon Take; Noor Azlin Yahya,; Muralithran Govindan Kutty, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Lithium disilicate are commonly used in dental restoration due to its aesthetic and mechanical performance. However, the patent expiration of the IPS emax system has led to the emergence of other variations of the system. Data and studies concerning mechanical properties of these recent lithium disilicate-based CAD/CAM are scarce and it warrants for an investigation to provide scientific evidence to support its routine use. The aim of this study was to investigate and compare the mechanical properties of lithium disilicate-based CAD/CAM blocks from four different brands. Four CAD/CAM lithium disilicate brands were investigated; IPS emax, Mazic Claro, Cameo, and Tessera. Specimens (n=10) were prepared accordingly; for flexural strength (16 × 4 × 1.2 mm) and microhardness test (15 × 13 × 2 mm). One specimen from each brand was analysed for the microstructure, elemental composition and distribution before and after heat treatment using scanning electron microscope and energy dispersive x-ray spectroscopy. The three-point flexural strength test (n=10) and microhardness test (n=10) was performed. Data were analysed using one-way ANOVA and Dunnett’s T3 test. The results showed that the highest mean flexural strength was from Group 4 Tessera (540.52 ± 143.33 MPa). For microhardness, the highest mean was from Group 1 Mazic Claro (667.70 ± 9.41 HV). Within the four groups, statistically significant difference is noted for flexural strength and microhardness. As a conclusion, Tessera demonstrated significantly higher flexural strength than IPS emax and Cameo. Mazic and Tessera demonstrated significantly higher microhardness than IPS emax and Cameo. All materials tested were above the threshold of 300 MPa.